(untitled) (Community Based Medical Journal, 2026)
Twin pregnancies are associated with higher risks of maternal and fetal complications compared to singleton pregnancies. Understanding fetomaternal outcomes is crucial for improving prenatal care and reducing adverse events. A retrospective study was conducted at Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, focusing on twin pregnancies managed in the hospital between January and June of 2024, to evaluate the fetomaternal outcomes of twin pregnancies. A total of 37 twin pregnancies were selected through purposive sampling. Data was collected from hospital records and analyzed. Our study revealed that the mean gestational age at delivery was 35.2±2.1 weeks, with 64.9% preterm births before 37 weeks. Antenatal complications included preterm labour (43.24%), preeclampsia (24.32%), gestational diabetes (16.22%) and anaemia (18.92%). Caesarean deliveries (78.4%) were predominant. Neonatal outcomes showed 56.8% low birth weight and 10.8% perinatal mortality. Maternal complications occurred in 32.4% of cases, with postpartum haemorrhage (13.5%) being the most common. Those findings highlight the significant risks associated with twin pregnancy. We would like to emphasize the need for specialized antenatal care and delivery planning. High rates of preterm birth and perinatal complications underscore the importance of vigilant monitoring in twin pregnancy to optimize outcomes for both mothers and newborns. CBMJ 2026 January: vol. 15 no. 01 P:35-40